Accurate depolarization ratio measurements for all diatomic hydrogen isotopologues. (23rd April 2013) - James, T. M.; Schlösser, M.; Fischer, S.; Sturm, M.; Bornschein, B.; Lewis, R. J.; Telle, H. H.
Abstract : The Raman depolarization ratios for individual Q1 (J") branch lines of all diatomic hydrogen isotopologues – H2, HD, D2, HT, DT, and T2 – were measured, for all rotational levels with population larger than 1/100 relative to the Boltzmann maximum at room temperature. For these measurements, the experimental setup normally used for the monitoring of the tritiated hydrogen molecules at KArlsruhe TRItium Neutrino experiment was adapted to optimally control the excitation laser power and polarization, and to precisely define the Raman light collection geometry. The measured Raman depolarization values were compared to theoretical values, which are linked to polarizability tensor quantities. For this, the 'raw data' were corrected taking into account distinct aspects affecting Raman depolarization data, including (1) excitation polarization impurities; (2) extended Raman excitation volumes; and (3) Raman light collection over finite solid angles. Our corrected depolarization ratios of the hydrogen isotopologues agree with the theoretical values (based on ab initio quantum calculations by R.J. LeRoy, University of Waterloo, Canada) to better than 5% for nearly all of the measured Q1 (J") lines, with 1σ confidence level. The results demonstrate that reliable, accurate Raman depolarization ratios can be extracted from experimental measurements, which may be substantially distorted by excitation polarization impurities and by geometrical effects. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The Raman depolarization ratios for a wide range of individual Q1 (J") branch lines of all diatomic hydrogen isotopologues – H2, HD, D2, HT, DT, and T2 – were measured. The experimental ('raw') Raman depolarization values were corrected for polarization impurities in the laser excitation beam; for the extended excitation volume; and for Raman light collection over finite solid angles. These corrected Raman depolarization ratios agree to better than 5% with theoretical values based on ab initio polarizability tensor quantities.